ENTREPRENEURIAL MANAGEMENT IN INNOVATIVE PRODUCT AND BUSINESS DEVELOPMENT - G. Laptev (Управленческие науки, 2016)
Today entrepreneurship has extended farther than start-ups and it already covers different types of entities at almost all stages of their life cycle. Entrepreneurial management is targeted at seeking for and implementing new business opportunities to create the new value. Companies that operate under tough competition have increasingly been acquiring entrepreneurial character.The paper discusses the approach developed by Innovative Business and Entrepreneurship Laboratory at the Faculty of Economics, Lomonosov Moscow State University, in which the competencies of the entrepreneurial management are used to manage the completely uncertain initial stage in the process of creating an innovative product. The step is crucial for creating a marketable innovative product. It is here where the concept and the main engineering requirements for future products are built. The main complexity for creators lies in the fact that in case of a really new (innovative) product marketing tools practically do not work at this stage of the product development. The fact is that consumers live in today’s paradigm and, for the most part, are not able to dip beyond the horizon of existing products.The paper proposes an iterative model for the creation of an innovative product at the initial stage, which consists of three phases: identification of opportunities generating and testing product ideas rapid creating and testing the least possible viable product - a product with a minimal permissible set of features sufficient for users to pay for. Based on the developed practice, the paper formulates the set of essential managerial actions to efficiently manage the process of creating an innovative product at theinitial stage. Competencies (knowledge, skills and capabilities) play a key role in consumers’ developmentin entrepreneurial management at early stages, providing them with an essential innovative product and a profitable/scalable business model. The paper presents critical competencies which are the most difficultto develop in the entrepreneurial management, the latter being concentrated in the two clusters: those of thought and personality.